Organizational culture and constructions of the customer - Alvesson, Mats, 1956- (SAGE knowledge. Cases., 2016)
The case is based on an ethnographic study of the editorial wing of a Swedish evening newspaper. It examines the newspaper's organizational culture and its influence on marketing and the construction of the customer.